A cashflow-at-risk approach to leasing industry : Empirical evidence from the Turkish leasing sector - Akpınar, Cüneyt (My University, 2012)
nancial Leasing, Operational Leasing, Value-at-Risk, Cash Flow-at-Risk. The study aims at introducing a risk management framework for the Turkish leasing industry and analyzes the impact of the new leasing legislation in terms of potential risk and returns. The study is an integrated one that employs a holistic approach to the leasing sector. Leasing is an alternative financing means, in particular, for SMEs. Since SMEs are locomotive of economic growth and stability, financing is always attached great importance. However, with technological development, typical financial tools are not sufficient to support economic activities. As well as its profitability, leasing industry also harbors some risks. Main risks are liquidity risk, due to the nature of the assets (heavily its property, plant and equipment) and the mismaturity in the balance sheets. With global change, rapid development, and intense competition, industry becomes riskier. Therefore, it is crucial to study risk management from the perspective of the lessor. The study employs a new risk quantifying methodology, namely Cash Flow-at-Risk methodology. This is a significant contribution of the study. In addition, a new legislative framework in Turkey is expected to introduce operational leasing in addition to financial leasing for BRSA supervised financial leasing companies. Accordingly, the study also employs sensitivity analysis to measure potential impact of the introduction of operational leasing, partially or fully by the financial leasing companies. The study concludes that an optimal allocation of financial and operational leasing would balance the risk and returns in the leasing industry over the long-term.
Keywords: Muhasebe